(3TQM efXheI GdHjbhfi aj Yde eUWdM GdMOjKs - (3eMeO Hf YHO GdHGbi GdRQbGfis; (3GdHjbhfjs ((3eMeO NdGa Hf eMeO eUWai Gdefhai s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdYRjR Gdbhi GdZGaQ , GdPi fVQ CUMGH GdMOjK , hMSfge ai GdbOje hGdMOjK CeG HYO abO SCdfi HYV GdENhGf Cf CTQM dg efXheI GdHjbhfi ai eUWdM GdMOjK s
(3BNQgG (B:s
(3haQZJ ef JShjOgG ai jhe YGThQkG ai SfI KeGfjf hCda hbO aQZJ ef JHjjVgG YTjI jhe YQaI Yai Gddg Yfg Bejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ajgG eJf GdHjbhfjI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs